Islamic Pacifism in the Middle East: Khalis Jalabi as a Proponent of Post-Islamist Ethics - Abdessamad Belhaj (Journal of Asian Wisdom and Islamic Behavior, 2026)
Over the past 20 years, research on Islamic pacifism, particularly in its post-Islamist branch, has considerably expanded. The recent Islamist violence has compelled many researchers to explore and examine the moral underpinnings of Islamic pacifism. Nevertheless, no research has been conducted on the contribution of the Syrian thinker Khāliṣ Jalabī (born in 1945). Yet, Jalabī's criticism of Islamist violence, his work on the need for societal change, and the requirement of a scientific-historical approach to the Islamic legacy are all very significant and deserve careful consideration. Through a textual analysis and critical engagement, this article studies the promises and limitations of his post-Islamist ethics, especially in the current transformations in Islamic thought.